Cover Feature: A Pyridoindole‐Based Multifunctional Bioprobe: pH‐Induced Fluorescence Switching and Specific Targeting of Lipid Droplets (Chem. Asian J. 18/2017). Issue 18 (4th September 2017) - Sk, Bahadur; Thakre, Pilendra Kumar; Tomar, Raghuvir Singh; Patra, Abhijit
Abstract : What a PITE ! A multifunctional fluorescent bioprobe based on pyridoindole (PI) and tetraphenylethylene (TE), PITE, showing pH‐responsive fluorescence switching in solution, as nanoparticles and in the solid state that can be used to sense toxic organic acid vapor is presented. Hydrophobic nanoparticles of PITE turned out to be highly specific for the imaging of lipid droplets (LDs) in diverse organisms. Selective targeting of LDs by PITE in lower eukaryotes, such as yeast, and in mammalian cells both in vivo and in vitro show the potential of PITE for real‐time tracking of LDs under pathophysiological conditions. More information can be found in the Full Paper by Raghuvir Singh Tomar, Abhijit Patra et al. onpage 2501 in Issue 18, 2017 (DOI:10.1002/asia.201700898 ).